A indústria 4.0 e as mudanças no mundo do trabalho e da Educação: qualificação e precarização - Sousa, Ana Paula de Castro (2023)
This thesis was developed in the Graduate Program in Education, of the Federal University of Uberlândia, in the research line Work, Society and Education, in the research group Work, Education and Society (GPTES), under the title: “Industry 4.0 and changes in the world of work and education: qualification and precarization”. Such a theme, Industry 4.0, is identified as the integration of new and emerging Information and Communication Technologies (ICTs). These new technologies constitute the space of production, stimulate massive gains in productivity and flexibility, and change the nature of industrial work. Still, the changes of Industry 4.0 affect the entire business, political, economic and social environment, having been labeled as the Fourth Industrial Revolution. This study has the general objective of analyzing industry 4.0 and changes in the world of work and education, focusing on qualification and precarization. Therefore, its specific objectives are: – to analyze the historical and technological development of the 1st and 2nd Industrial Revolution, based on the concept of cooperation discussed in 'Work and Technology in Marx and the Subordination of Labor to Capital' (Chapter I) ; – to identify the changes in working conditions in the technological sector of the 3rd and 4th Industrial Revolution and to analyze the concept of qualification in Braverman, according to 'Work and professional qualification...” (Chapter II); – to identify Theory of Value and Immaterial Labor on the Digital Platforms of Google and Facebook Companies”, in order to understand how value generation has been taking place in these companies and the ways undertaken to control work (Chapter III); – to analyze Industry 4.0 and the changes it has been promoting in the Brazilian labor market, based on the ‘Professional Qualification for the new world of work’ (Chapter IV). The hypothesis that guides this research is that there is a discourse of neutrality and effectiveness of the new Information and Communication Technologies (ICTs) that is not verified in concrete reality. The justification of this research is justified as it sheds light to the technological movement through questions about the repercussions of Industry 4.0, as a sociotechnical change in the world of work, on the worker and their qualifications. The theoretical foundation lies on Marx's historical-dialectical materialism, in order to understand the contradictions of the historical process to which the object belongs, as well as its possible implications regarding working and living conditions, and their consequences. For that, a bibliographical research was carried out on the subject, in order to bring the debate around technological progress, scientific knowledge and qualified work. With this purpose, Ricardo Antunes, Harry Braverman, Ursula Huws, Edwards and Ramirez, were analyzed. Frey and Osborne, Firdausi, Azhar Sharan in the critical perspective and Gerkhe, Klaus Schwab defenders of technological neutrality were also analyzed. The time frame analyzed was from 2011 to 2023.